2020
DOI: 10.3390/ijerph17176076
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity Counseling for Adults with Hypertension: A Randomized Controlled Pilot Trial

Abstract: The effect of physical activity counseling (PAC) in hypertensive adults is unclear. This study investigated the effect of PAC on blood pressure (BP), physical activity level, sitting time, metabolic profile, and body composition in hypertensive adults. Twenty-two hypertensive adults (48.8 ± 7.3 years) participated in this pilot trial. The 12-week PAC was based on the 5 A’s model considering the FITT principle (Frequency, Intensity, Time, and Type) of physical activity. The control group received instructions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
0
5
0
1
Order By: Relevance
“… 62 Example of Brief Action Planning Brief Action Planning Certification Publication Explaining the Development and Steps of Brief Action Planning 5A's and 5R's - time requirement variable Patients seen by clinicians who used the 5A's had higher physical activity levels ( P =.01), higher daily step counts ( P =.04), and lower sitting time ( P =.05). 63 , 64 Effectiveness and efficacy studies are primarily from smoking cessation literature. 65 US Preventative Taskforce World Health Organization's Training Modules …”
Section: A Theoretical-based Clinical Decision Pathway That Incorpora...mentioning
confidence: 99%
“… 62 Example of Brief Action Planning Brief Action Planning Certification Publication Explaining the Development and Steps of Brief Action Planning 5A's and 5R's - time requirement variable Patients seen by clinicians who used the 5A's had higher physical activity levels ( P =.01), higher daily step counts ( P =.04), and lower sitting time ( P =.05). 63 , 64 Effectiveness and efficacy studies are primarily from smoking cessation literature. 65 US Preventative Taskforce World Health Organization's Training Modules …”
Section: A Theoretical-based Clinical Decision Pathway That Incorpora...mentioning
confidence: 99%
“…However, for a similar intervention implemented by non-health professionals (peer health facilitators, exercise trainers) this review found a significant positive effect on physical activity [ 97 ]. Likewise, a recently published pilot study suggested that physical activity counselling for 14 weeks increases the number of steps taken per day, but has no effect on the blood pressure of hypertensive patients [ 98 ]. Significant effects on blood pressure of hypertensive patients can be expected when physical activity is combined with dietary counselling [ 99 ].…”
Section: Physical Activitymentioning
confidence: 99%
“…Zdá se, že klíčem může být celková a fyzická aktivita během dne, kdy koreluje pokles krevního tlaku s celkovým množstvím kroků za den (6). Naopak se ukazuje, že obvyklé doporučované fyzické aktivity podle obecných zásad nemají skoro žádný efekt na krevní tlak, či metabolické parametry, protože dochází k jen mírnému navýšení fyzické aktivity (7). Nicméně jsme již v minulosti prokázali i na českých datech, že "sportující" osoby mají významně nižší výskyt hypertenze než nesportující se stejným BMI (8).…”
Section: Fyzická Aktivita a Hypertenzeunclassified